Elevated Peripheral T Helper Cells Are Associated With Atrial Fibrillation in Patients With Rheumatoid Arthritis - Wang, Xin; Fan, Hongxuan; Wang, Yongle; Yin, Xufang; Liu, Guangying; Gao, Chong; Li, Xiaofeng; Liang, Bin (Frontiers in Immunology, 2021)
Patients with rheumatoid arthritis (RA) have a significantly high risk of atrial fibrillation (AF). This study aimed to compare the absolute and relative changes in peripheral T cells in patients with RA, who were also affected with and without AF. To help make an early diagnosis and prevent the initiation and progression of AF, the changes in the lymphocyte subsets were assessed in RA patients with and without AF. A propensity score matching system (PSM) (1:3) was used to perform a matched case-control study with 40 RA-AF cases and 120 RA controls. Changes in the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), anti-cyclic citrulline peptide antibody (ACPA), and rheumatoid factor (RF) were examined. The percentage and absolute number of T, B, natural killer (NK), T-helper (Th) 1, Th2, Th17, and T-regulatory (Treg) cells in the peripheral blood of patients with and without RA-AF were determined using flow cytometry. Univariate and multivariate analyses were performed to determine the association between peripheral lymphocytes and RA-AF. Demographic data, ESR, CRP, ACPA, and the percentage, as well as the absolute value of B, NK, Th2, and Treg cells, showed no significant differences between the propensity score-matched groups of RA and RA-AF. Meanwhile, the absolute number and percentage of Th1 cells, the absolute number of Th17 cells, the ratio of Th1/Treg, Th17/Treg, and RF were significantly higher in patients with RA-AF than those in the control groups (P <0.05). Univariate and multivariate logistic regression analyses also revealed that the percentage of Th1 cells, the absolute number of Th17 cells, and the ratio of Th1/Treg were associated with a significantly higher risk of AF. This PSM study demonstrated that the incidence of AF was higher in RA patients with T helper cell immunological derangements.